An analysis of the relationship between leisure participation and perceived quality of life - Paul N. Acha-Anyi; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
This study explores the relationship between leisure participation and perceived quality of life among respondents in the Eastern Cape province of South Africa. Using a cross-sectional research design, data were collected from 247 participants at four community events. The results reveal a positive relationship between leisure participation and perceived quality of life. However, no statistically significant differences were found between selected independent variables and quality of life, and the effect sizes indicated minimal impacts. In view of the positive effects of leisure involvement on perceived quality of life, the study recommends, inter alia, that the government play a leading role in encouraging leisure practice through policy implementation within communities.
Keywords: 330; Leisure participation; quality of life; Eastern Cape province; South Africa